How Competitive Are Crop Markets in Sub‐Saharan Africa?. (16th August 2017) - Dillon, Brian; Dambro, Chelsey
Abstract: During the structural adjustment era of the 1980s and 1990s, governments across sub‐Saharan Africa generally withdrew from crop markets to encourage entry by private traders and foster competition. Since that time, the degree of competition in crop markets has been a central concern of policymakers, donors, and researchers. We review the evidence on that topic by first developing a conceptual framework to guide our analysis, then discussing the findings from four categories of literature. We have two main findings. First, there is a paucity of empirical evidence on this question, which hinders our ability to draw strong conclusions. Second, that point notwithstanding, the evidence that does exist is broadly supportive of the notion that crop markets are competitive. The dominant themes in the literature are that trading profits are highly variable, trader entry and exit rates are high, and price co‐movements between markets suggest relatively efficient levels of competitive arbitrage. It is possible that the high costs of entry foster non‐competitive conditions at the level of large‐scale, long‐distance subnational trade, but we find no positive evidence to that effect, only the satisfaction of certain necessary conditions.